RATE AND RISK FACTORS FOR SURGICAL SITE INFECTION AT A TERTIARY CARE FACILITY IN PESHAWAR, PAKISTAN - Khan, Mansoor; Khalil, Jawad; Muqim, Rooh -ul-; Zarin, Mohammad; Hassan, Touseef Ul; Ahmed, Nisar; Salman, Muhammad; Muhammad, Ghulam (Journal of Ayub Medical College Abbottabad, 2011)
ackground: Surgical site infections (SSI) are among the most common complications in surgical patients and have serious consequences for outcomes and costs. This study aimed to determine the rates and risk factors affecting surgical site infections and their incidence at Surgical '˜C' Unit, Khyber Teaching Hospital, Peshawar, Pakistan. The study was conducted to compare with rates obtained by large international multi-centre studies. Methods: A review of all general surgical interventions involving an incision, excluding anal procedures, performed between December 2008 and March 2009 (n=269) was undertaken. Various clinical parameters were recorded. Infection rates were calculated. Data were analysed using the Fisher's exact test. Results: The overall SSI rate was 9.294%, 4.88% in clean cases (C), 8.39% in clean contaminated cases (CC), and 20.45% in contaminated or dirty cases (D). There were significantly higher surgical site infection rates among patients with combined American Society of Anaesthesiologists scores II and III than those with ASA score I in clean contaminated (p=0.0007), and dirty cases (p=0.0212). There were also significantly higher surgical site infection rates among patients with combined Co-morbidity Scale score 1-6 than those with no comorbid factors in clean contaminated (p=0.0002). Surgical site infection rate was highest in gastrointestinal system surgeries. Conclusion: The Surgical site infections can be minimised by adopting international protocols for surveillance. Keywords: Charlson Co-morbidity Index, Surgical Site Infection, Clean, clean-contaminated and dirty surgeries; Risk factors